(untitled) (GAIMS Journal of Medical Sciences, 2024)
Background: Neonatal seizures are the most common neurological emergencies encountered in newborns. Neonatal seizures are poorly classified, under-recognized and often difficult to treat. The present study is aimed to find out the spectrum of causes of neonatal seizures with its relationship to various parameters like gestational age, etiology, seizure type. Material and methods: This Hospital based observational, cross-sectional study was conducted in the level-II Neonatal Intensive Care Unit of Department of Pediatrics, Jawaharlal Nehru Hospital and Research Centre Bhilai, Durg, Chhattishgarh for One year (December 2019 –November 2020). Sample size was 110. The parents of admitted newborns were approached and consent was taken. Study subject were selected as per above mentioned inclusion and exclusion criteria. All cases included in this study were evaluated on following parameters-History, Physical Examination & Measurement of laboratory parameters. Results: The above table shows the detailed demographic details of our study group in relation to sex, maturity and birth weight. Amongst our 110 subjects with seizures, we had a total number of male neonates in our study were 61 (55.45%), and female neonates were 49 (44.55%). Conclusion: Our incidence of neonatal seizures in hospitalized NICU was 3.32%. The male to female ratio in our study was1.2:1. The most common cause of neonatal seizures in our study was birth asphyxia, followed by metabolic abnormalities. This was followed by meningitis. Birth asphyxia was the most common cause of seizures in preterm cases. The metabolic abnormalities (hypoglycemia,hypocalcemia and hypernatremia) were the most common cause of seizures in term neonates.